ROSYJSKIE SEMINARIUM PRAWA RZYMSKIEGO PRZY BERLIŃSKIM UNIWERSYTECIE - Zieliński, Marcin (Zeszyty Prawnicze, 2016)
The Russian Seminar of Roman Law at the University of Berlin and its Polish Participants Summary After the university reform of 1884 in the Russian Empire there was a need to educate more scholars of Roman law for appointments to vacant chairs. The tsar’s government in cooperation with University of Berlin established a special institution in Berlin called the Russian seminar of Roman law. This seminar was intended for graduates of Law and Classics. Distinguished German professors of Roman and civil law, H. Dernburg, A. Pernice, and E. Eck, were tutors to the tsar’s students. The prescribed course of lectures took two years and students had to write a final dissertation. Some of the tsar’s students were of Polish origin, and they included L. Petrażycki, who was probably the most renowned, K. Dynowski, T. Siemiradzki, and W. Juszkiewicz. Later only Dynowski and Juszkiewicz continued their interest in Roman law. Petrażycki became a famous scholar of the theory and sociology of law. Siemiradzki did not finish the seminar, because he conspired against the tsar’s government in a Polish underground organisation in Berlin and the Russian government sent him to prison.